Raindrop in the drought? Vulnerability to climate shocks and the role of social protection in Zambia - Katrin Gasior; Pia Rattenhuber; Adnan Shahir; Anna Zasova (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
Zambia's reliance on rain-fed agriculture makes its economy and population highly vulnerable to frequent droughts and irregular rainfall. This paper assesses the role of social protection, specifically the Social Cash Transfer (SCT) program, in mitigating drought-induced poverty and consumption declines. Using the MicroZAMOD microsimulation model and districtlevel rainfall data, we find that rainfall shocks significantly increase poverty and reduce household consumption, disproportionately affecting the poorest households. While the current SCT program provides some relief, reforms to eligibility criteria, particularly removing the household composition requirement, could improve targeting, expand coverage, and strengthen resilience against climate-related economic shocks.
Keywords: H84; I38; Q54; 330; Zambia; tax-benefit microsimulation; social protection; climate change